Avaliação do PIB, da frota de veículos e da extensão de rodovias no consumo energético e emissões de dióxido de carbono do transporte rodoviário do Brasil - Nicolau, Olivia Nascimento Boldrini (2018)
The transportation sector is a key sector for the development of a country, since it is a support for the economic and social development of a nation. However, it is a sector that has a large amount of energy from fossil fuels that generate volumes considered as greenhouse gases. In 2016, the sector was responsible for 29% of CO2 emissions in Brazil, 90% of this total being related to road mode. Given the importance of the sector and its polluting potential, this work aims at the energy consumption and, consequently, the CO2 emission of the road way in Brazil. For this, the System Dynamics (SD) method was chosen. Initially, relations between markets, GDP (global and transportation sector) and investments in road (road extension) were structured through a cause and effect diagram and then elaborated by a stock and flow diagram. With the proposed model, 15 scenarios were defined, among which were evaluated over a eleven year horizon, between 2016 and 2026, from various perspectives. The effects show that the variation of the road vehicles has a greater influence on the energy consumption and, consequently, the CO2 emissions, when compared to the composition of fuel use and investments in road paving. A. This indicator showed that there is a significant gain in increasing the productivity of the sector in relation to the reduction of sales caused by the increase of the fleet of vehicles. In view of the above, becoming a more efficient energy object, a transportation sector, is more a road case, it is a problem that can be discussed, have a greater probability of economy and its environmental impact without the development of a country, mainly in nations What to do as this view represents 60% in the transport matrix.